Phenomenology Study: Pregnancy Women Myth in Malay Community Dumai City, Indonesia - Ismainar, Hetty; Hertanto W. Subagio,; Bagoes Widjanarko,; Cahyono Hadi, (Technium Social Sciences Journal, 2020)
This study aims to analyze the pregnant women myths in the Malay community of Dumai City, Indonesia. The qualitative research: Phenomenology Study. The total informants were 11 participants (Pregnant women, shaman, midwife, and Primary Health Care Heads). Data collection through in-depth interviews and non-participant observation. Data analysis uses content analysis. The results showed that three things were during pregnancy, namely: cultural tradition in pregnant, food consumption, and activities. That even for pregnant women in “Lenggang Perut” (seven months pregnant ceremony). Use porcupines, scissors, and needles in the body to avoid the devil. Cannot consume sugar water from “Tebu” (a kind of sweet plant), pineapple, and “Tape” (food from cassava fermentation) because it will cause bleeding or abortion. Prohibited activities, bathing at night, sitting in front of the door, for early gestation may not leave their homes and still visit shamans. Until now, this myth is still practiced by pregnant women in the Malay community, although there is no empirical research that proves the real impact of the myth.